Extensive Margin Adjustment of Multi-Product Firm and Risk Diversification - Carvalho, Carlos (IMF Working Papers; Working Paper ;, 2017)
Product scope adjustment is a key mechanism through which multi-product firms achieve efficient resource allocations. In this paper, we take a novel perspective to study firms' product scope adjustment behavior through the lens of asset pricing. Using a unique panel scanner data set containing detailed information on products, matched with the financial information of their manufacturers, we find that multi-product firms with higher product turnover have lower financial risks and lower risk premia. To understand this channel, we propose a stylized model with a time-dependent (Calvo-type) product turnover rate to highlight the 'risk absorption channel' of product scope adjustment. In response to an economy-wide shock, a firm that can adjust its product scope more flexibly shows lower excess equity returns and lower asset volatility.